Pengaruh Bimbingan Kelompok Tkenik Problem Solving terhadap Pemiliihan Studi Lanjut - Hasan, Muhammad Zaenul; Karamoy, Yurike Kinanthy; Mutakin, Fakhruddin (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
Choosing the level of education after completing junior high school is a crucial decision for grade IX students that will affect their future. However, many students feel confused or unsure. According to what happened at MTS Bustanul Ulum Panti, it shows that there are 5 students who have not been able to determine their further studies. The purpose of this study is to determine the influence of group guidance on the selection of further studies. This study uses a quantitative approach to the One Group Pretest Posttest experimental study. The results showed that the average score before the intervention was 71.00, while the average score after the intervention was 96.00. The significance result (two-sided) yields a value of 0.000. If the calculated t-value exceeds the t-value of the table or the significance value is below 0.05, then an alternative hypothesis (Ha) is accepted which indicates an influence. On the other hand, if the calculated t-value is less than the t-value of the table or the significance value is greater than 0.05, then the null hypothesis (Ho) is rejected and has no effect. The null hypothesis was rejected because the significance value (two-sided) was less than 0.05, meaning that there was a significant difference in the mean results before and after. Thus, a conclusion was obtained: The influence of group guidance of problem solving techniques on the selection of further studies of students